2021
DOI: 10.3390/jpm11100994
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pulmonary Function Decline over Time with Longitudinal Change of Glycated Hemoglobin in Participants without Diabetes Mellitus

Abstract: Pulmonary damage and function impairment were frequently noted in patients with diabetes mellitus (DM). However, the relationship between lung function and glycemic status in non-DM subjects was not well-known. Here, we evaluated the association of longitudinal changes of lung function parameters with longitudinal changes of glycated hemoglobin (HbA1c) in non-DM participants. The study enrolled participants without prior type 2 DM, hypertension, and chronic obstructive pulmonary disease (COPD) from the Taiwan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Possible pathological processes associated with impaired pulmonary function in T2DM may include non-enzymatic glycosylation of lung elastin structures, which could stiff the lung [40] and cause a restrictive impact on ventilation; and diabetes-induced microvascular complications, which could impair the diffusion [37,41] and diminish gas exchange. It is reported that lung function assessed by forced vital capacity and forced expiratory volume in 1 sec (FEV-1) are inversely correlated with HbA1c [42][43][44] and DLCO is significantly impaired in patients with T2DM [44]. Furthermore, patients who have poor glycemic control with HbA1c >7% show lower DLCO or the ratio of DLCO to alveolar ventilation compared to the counterparts with HbA1c <7% [44].…”
Section: Taichi Improved Pulmonary Diffusion Capacity In T2dmmentioning
confidence: 99%
“…Possible pathological processes associated with impaired pulmonary function in T2DM may include non-enzymatic glycosylation of lung elastin structures, which could stiff the lung [40] and cause a restrictive impact on ventilation; and diabetes-induced microvascular complications, which could impair the diffusion [37,41] and diminish gas exchange. It is reported that lung function assessed by forced vital capacity and forced expiratory volume in 1 sec (FEV-1) are inversely correlated with HbA1c [42][43][44] and DLCO is significantly impaired in patients with T2DM [44]. Furthermore, patients who have poor glycemic control with HbA1c >7% show lower DLCO or the ratio of DLCO to alveolar ventilation compared to the counterparts with HbA1c <7% [44].…”
Section: Taichi Improved Pulmonary Diffusion Capacity In T2dmmentioning
confidence: 99%